2019
DOI: 10.1101/592014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Damage to the Right Insula Disrupts the Perception of Affective Touch

Abstract: Specific, peripheral C-tactile afferents contribute to the perception of tactile pleasure, but the brain areas involved in their processing remain debated. We report the first human lesion study on the perception of C-tactile touch (N = 59), revealing that posterior and anterior right insula lesions reduce tactile, contralateral and ipsilateral pleasantness sensitivity, respectively. These findings are consistent with a posterior-to-anterior pattern of integration of interoceptive information in the frontoinsu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Cerebral lesions specifically involving the dorsal posterior insula disrupt touch pleasantness delivered at CT optimal velocities. 4 These findings imply that Aβ- and CT-LTMR pathways are distinct with CT afferents being placed within a wider system that is more interoceptive than exteroceptive. 1,3…”
mentioning
confidence: 92%
“…Cerebral lesions specifically involving the dorsal posterior insula disrupt touch pleasantness delivered at CT optimal velocities. 4 These findings imply that Aβ- and CT-LTMR pathways are distinct with CT afferents being placed within a wider system that is more interoceptive than exteroceptive. 1,3…”
mentioning
confidence: 92%
“…CTs optimal firing response to gentle skin stroking, when recorded during microneurography studies (Löken et al 2009), is between 1-10 cm/s, corresponding to selfreported pleasant perception of touch as measured psychophysically (Essick et al, 2010), leading to the hypothesis that CTs have evolved in all social mammals to encode the socio-affective and rewarding dimensions of touch (Morrison et al, 2011). Interestingly, a recent lesion study which has investigated deficits in the perceived affectivity of CT optimal touch has found that posterior and anterior right insula lesions reduce pleasantness sensitivity in perceiving CT-optimal touch (Kirsch et al, 2020). Cutaneous afferent C-fibers are a diverse population of unmyelinated, slowly conducting nerves that evolved primarily to provide a basic function of protection by detecting and transmitting information to the brain of negatively hedonic (i.e., nociceptive, pruriceptive) events from the skin of the body or viscera, or of positively hedonic (affiliative touch) events.…”
Section: The Role Of Affectionate Touch In Infancymentioning
confidence: 99%
“…For instance, Gordon et al ( 48 ) showed that CT–targeted affective touch to the arm activated the insula and the mPFC/dorsal–anterior cingulate cortex (dACC). Lesions of the insula in turn, impair the perception of affective touch ( 49 ). Recently, the insula was shown to be also activated by A-beta afferents ( 50 ).…”
Section: Introductionmentioning
confidence: 99%